Development Tourism Geographic Information System of Samarinda - Agung Wiyanda; Suswanto; F. V. Astrolabe Sian Prasetya (TEPIAN, 2022)
This research is motivated by the low level of dissemination of tourism information in the city of Samarinda. Samarinda is one of the cities with very diverse and interesting tourism potentials to explore. The beauty of the urban area and being one of the cities that is crossed by the largest river in the province of East Kalimantan, namely the Mahakam river, makes it one of the tourist destinations that has its own charm, but unfortunately at this time the tourism places in the city of Samarinda have not been widely publicized due to lack of information. About tourism that is given to the public and there are also some places that have not been or have just been opened to become tourist sites. This study uses spatial data in the form of location coordinates and non-spatial data in the form of attribute data including tourist names, addresses, and types of tours, descriptions and pictures. Making the Samarinda City Tourism Geographic Information System website using the Leaflet API as a base map. The database created using PHPMyAdmin on the Samarinda City Tourism Geographic Information System is based on collecting secondary data on tourism information at the Samarinda City Tourism Office and also collecting primary data by interviewing tourist objects that have not been recorded at the Samarinda City Tourism Office. The system and appearance of the Samarinda City Tourism Geographic Information System website was built with the CodeIgniter 3 framework using Visual Studio Code as a text editor. The results of this study are the Samarinda City Tourism Geographic Information System which provides information on tourist names, addresses, types of tours, location coordinates, descriptions, images and is equipped with search features and also road routes to tourist sites. It is hoped that the Samarinda City Tourism Geographic Information System can provide adequate information about tourism information in the city of Samarinda so as to facilitate the delivery and acceptance to the public, especially prospective tourists.